Indelible shadows : film and the Holocaust - Insdorf, Annette (Cambridge University Press, 2003)
Finding an appropriate language. The Hollywood version of the Holocaust ; Meaningful montage ; Styles of tension ; Black humor -- Narrative strategies. The Jew as child ; In hiding/onstage ; Beautiful evasions? ; The condemned and doomed -- Responses to Nazi atrocity. Political resistance ; The ambiguity of identity ; The new German guilt -- Shaping reality. The personal documentary ; From judgment to illumination -- Third edition update. The Holocaust as genre ; Rediscoveries ; Rescuers in fiction films ; The ironic touch ; Dysfunction as distortion: the Holocaust survivor on screen and stage ; Documentaries of return